2018
DOI: 10.4103/eus.eus_22_17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of pancreatic cyst fluid changes clinical management

Abstract: Background and Objectives:DNA molecular analysis has been suggested as a tool to evaluate pancreatic cysts. This study assesses whether the addition of DNA molecular analysis alters clinical management.Methods:This is a retrospective review of 46 consecutive patients who underwent EUS-FNA of pancreatic cysts with DNA molecular analysis at two major academic institutions. Cases were presented to two pancreaticobiliary surgeons first without and then with DNA molecular analysis data. The primary outcome was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…A study carried out by Arner et al [ 106 ] mentioned that “The addition of DNA molecular analysis alters the clinical management of PCLs most often when CEA levels are intermediate (45-800 ng/mL) or when no CEA concentration is available”.…”
Section: The Future Research Directions In the Diagnosis Of Cystic Pancreatic Lesions And The Role Of Molecular Analysis Of Pancreatic Cymentioning
confidence: 99%
“…A study carried out by Arner et al [ 106 ] mentioned that “The addition of DNA molecular analysis alters the clinical management of PCLs most often when CEA levels are intermediate (45-800 ng/mL) or when no CEA concentration is available”.…”
Section: The Future Research Directions In the Diagnosis Of Cystic Pancreatic Lesions And The Role Of Molecular Analysis Of Pancreatic Cymentioning
confidence: 99%
“…Previous studies that added next-generation sequencing (NGS) data to cytology exhibited a higher sensitivity (94.1% vs 87.1%) and specificity (100% vs 50%) compared with cytology alone for the detection of mucinous neoplasms and, in part, the detection of high-grade lesions[ 16 ]. Another study reported that the addition of molecular analysis altered disease management in approximately 25% of the patients and 40% of the cases when carcinoembryonic antigen levels were undetermined[ 17 ]. Several studies performed a molecular genetic analysis of cystic fluid based on RNA obtained using EUS-FNA used various methods of material transport and storage[ 4 , 18 ].…”
Section: Introductionmentioning
confidence: 99%